Application of the Oily-Bubble flotation of Shengli lignite and its optimization. Issue 3 (4th March 2022) - Chen, Songjiang; Tang, Longfei; Gui, Dongjiao; Chen, Liang; Tao, Xiuxiang; Zhu, Xiangnan
ABSTRACT: The upgrading of low-rank coal is important for its utilization. The lignite used in this study had extremely low surface hydrophobicity and responded poorly to the conventional flotation process. Therefore, to enhance its flotation, a laboratory device known as oily-bubble flotation was used. With this device, the combustible matter recovery at a collector dosage of 6.4 kg/t reached 32.94% which was comparable to that of the conventional flotation at the collector dosage of 50 kg/t. For improving recovery, utilization of electrochemical conditions for pulp, i.e., pH, and NaCl and CaCl2 solutions, was used to further enhance the oily-bubble flotation performance. Based on the response-surface methodology, a functional model for combustible matter recovery was established, and the regulator scheme in oily-bubble flotation was optimized to achieve a combustible recovery of 59.19% with pH and NaCl and CaCl2 concentrations of 6.03, 61.26 mmol/L, and 80 mmol/L, respectively. Results showed that an increased combustible matter recovery of 78.69% could be obtained using this optimization scheme.